1991
DOI: 10.1111/j.1755-3768.1991.tb04849.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular microdialysis with permanently implanted probes in rabbit

Abstract: The technique of microdialysis in vivo, much used in brain experiments, has been adapted for intraocular use. A new probe was designed, made from a soft tube with the dialysis membrane mounted in a fenestrated protecting sleeve, facing one side. A special surgical procedure was developed for the long-term implantation of the probes. They stay functional in the eyes for several weeks or more. Previously published intraocular microdialysis studies were short-term experiments. The acute surgical trauma is likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Microdialysis has been employed as an analytical tool for the determination of bioavailability of ocularly administered drugs in vitreous [19,20], retina [21], and aqueous humor [22][23][24][25]. Determination of aqueous humor samples traditionally has been conducted with paracentesis sampling of multiple animals at each time point.…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis has been employed as an analytical tool for the determination of bioavailability of ocularly administered drugs in vitreous [19,20], retina [21], and aqueous humor [22][23][24][25]. Determination of aqueous humor samples traditionally has been conducted with paracentesis sampling of multiple animals at each time point.…”
Section: Introductionmentioning
confidence: 99%
“…After general anesthesia induction, the eyelids of each rabbit were fixed with a folder. The conjunctiva was incised following the method of Waga et al (1991). The eye was fixed with the aid of sling sutures around the rectus superior and inferior muscles.…”
Section: Positioning Of Electrodesmentioning
confidence: 99%
“…[18][19][20][21][22] Moreover, conscious animal model for ocular microdialysis has already been developed and validated. 17,[23][24][25][26][27] Studies from our laboratory have demonstrated the effect of probe implantation in the rabbit eye on vitreal protein levels and pharmacokinetics. 17,23 The studies have also validated the method of such probe implantation and recommended that the appropriate recovery time must be allowed before commencing any pharmacokinetic study in conscious animal model.…”
Section: Introductionmentioning
confidence: 99%